Parapharyngeal Space Venous Malformation: An Imaging Mimic of Pleomorphic Adenoma - Tomblinson, C.M.; Fletcher, G.P.; Lidner, T.K.; Wood, C.P.; Weindling, S.M.; Hoxworth, J.M. (American Journal of Neuroradiology, 2019)
SUMMARY: Venous malformations in the parapharyngeal space are rare and may be challenging to diagnose with imaging secondary to multiple overlapping features with pleomorphic adenoma, which is much more commonly found in this region. While both lesions are T1 isointense and T2 hyperintense relative to skeletal muscle and demonstrate contrast enhancement, more uniform T2 hyperintensity and progressive contrast pooling on delayed postcontrast T1WI may allow the radiologist to include venous malformation in the differential diagnosis. This is important because it has the potential to alter management from surgical resection to observation. The primary aim of this study was to review the imaging appearance of parapharyngeal venous malformations through a retrospective case series.PPSparapharyngeal spaceVMvenous malformation